Facile Synthesis and Electrochemical Evaluation of Coumarin‐Tagged Pyridine and Thiophene Derivatives. Issue 8 (6th June 2016) - Alharthy, Rima D.; Hameed, Abdul; Rashida, Mariya al‐; Al‐Moubaraki, Aisha; Al‐Mhyawi, Saedah R.
Abstract: A series of coumarin pyridinethiones and pyridinones has been synthesized employing a range of substituted cyanothioacetamides and cyanoacetamides intermediates. Coumarin pyridinethiones and pyridinones bear different substituents including electron donating groups such as methyl, methoxy dimethylamine in addition to chloro, bromo and nitro as electron withdrawing groups were chosen to study the structure/electrochemical relationship. The influence of electron donating group and electron withdrawing group on different positions of coumarin scaffold was studied utilizing cyclic voltammetry and controlled potential electrolysis at platinum and glassy carbon electrodes. The electrochemical redox mechanisms of synthesized coumarins were proposed and the oxidation and reduction pathways were determined. Data for cyclic voltammetry and controlled potential electrolysis proved that amine center served as the oxidation center, while thiocarbonyl and carbonyl groups were identified as the reduction centers. Abstract : A series of coumarin derived pyridinethiones and pyridinones has been synthesized. The electrochemical properties have been studied using cyclic voltammetry and controlled potential electrolysis at Pt and glassy carbon electrodes. Substituent effects of electron withdrawing and electron donating groups at different positions of coumarin scaffold were explored to establish structure/electrochemical relationship profile. The electrochemical redox mechanisms of the synthetic coumarin analogues have been proposed. The electrochemical data suggests amine as oxidation center, and thiocarbonyl group as reduction center.